sUrVEI tUrN ArOUND tIME PADA PELAYANAN LABORATORIUM - Linda Rosita; O Sianipar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Turn Around Time (TAT) is time analysis check the laboratory started by since acceptance sampel still result and inclusive of result which have validated marked with the signature of laboratory doctor. TAT represents the important shares from medical service promisedTAT represents the important shares from medical service promised by laboratory party. Evaluate the TAT started from analysis to equipment of admission filling of request form of inspection laboratory.Evaluate the stuffing of request form met from the condition of sampel and telephone number which can be contacted nothing that filled. sampel and telephone number which can be contacted nothing that filled. and telephone number which can be contacted nothing that filled. TAT of better outpatient from at TAT of at patients take care. The monitoring of TAT shall have the character of the continue and ableThe monitoring of TAT shall have the character of the continue and able to give the feed back so that quality of good laboratory service progressively.